Artificial Intelligence-Based E-Learning in Chemistry Learning: A Review of Implementation in High Schools - Rahadian Zainul; Dony Novaliendry; Budhi Oktavia; Fitrah Mey Harmi Siregar; Maiti Faddila; Hidayatul Husna; Delsya Helvira Suci (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
This study analyzes the challenges and opportunities for implementing artificial intelligence (AI)-based e-learning in West Sumatra, with global and regional comparisons. Infrastructure gaps are a major obstacle, with 30% of the region lacking adequate internet access, especially in rural areas. In addition, 25% of teachers do not have adequate training in the use of AI technology, hampering the effectiveness of its implementation in schools. Other challenges identified are low digital literacy and limited access to technological devices, which impact 20-25% of schools. This study uses a comparative approach and the results are expected to provide insights and recommendations for policy makers in improving infrastructure, teacher training, and digital literacy, in order to accelerate the adoption of AI in education in West Sumatra.